How to assess doctor managers’ managerial attitude: results from an e-Delphi process - Americo Cicchetti; Federica Morandi; Ilaria Valentini; Fausto di Vincenzo (BMC Health Services Research, 2024)
Abstract Background Since the 1990s, healthcare systems in many Western countries, including Italy, have undergone significant reforms, transforming organizational models and structures to meet the growing demand for healthcare services efficiently. This transformation has introduced new managerial roles for doctors-managers, particularly at the midlevel, creating “doctor-manager” positions that involve both clinical and managerial responsibilities. However, doctor-managers often struggle to balance these dual roles due to a lack of formal managerial training and the inherent conflict between clinical and economic objectives. This study aims to define new evaluation dimensions that can enhance the existing scale and develop a new tool to assess the necessary components of the managerial attitude dimension required by doctor-managers in the current Italian healthcare system. Methods This study updated Cicchetti’s 2005 scale to reflect the changes that have occurred in healthcare organizations over the past 20 years, focusing on the evolving roles and challenges of middle healthcare managers. A scoping review was conducted to explore the existing literature, resulting in the identification and analysis of 24 key articles. Thematic analysis, facilitated by NVivo software, identified 171 items related to managerial attitude. These items were further refined, resulting in a 61-item Health Middle Manager Competencies Scale. The scale was evaluated by a Delphi panel through an e-survey, and Cronbach’s alpha was used to assess reliability. Results The final Competencies Scale for Middle Managers of Health consists of 61 items, validated by the Delphi panel of experts. The panel reached consensus on the relevance and significance of each item, confirming the scale’s reliability with an acceptable Cronbach alpha. The new scale captures various dimensions of the competencies essential for middle managers in healthcare settings. Conclusion The study provides insights into the dimensions of doctor managerial attitude and contributes to the update of Cicchetti’s Scale to develop a new tool that assesses all the necessary components now required within the managerial attitude dimension.